UPAYA MENINGKATKAN KEMAMPUAN BERCERITA DAN HASIL BELAJAR BAHASA JAWA TENTANG CERITA TOKOH WAYANG PADA PESERTA DIDIK KELAS IV SDN BULU DI SEMESTER I TAHUN PELAJARAN 2017/2018 DENGAN METODE GALLERY WALK - Sukarti, Sukarti (Widya Wacana: Jurnal Ilmiah, 2018)
Abstract The purposes of this research are 1) describing the Javanese Language about the Story of Shadow Puppets on the Class IV students of the Elementary School of Bulu on the first semester of 2017/2018 year academic with Gallery Walk Method and analyzing telling story ability and learning result Javanese language about the Story of Shadow Puppets on the Class IV students of the Elementary School of Bulu on the first semester of 2017/2018 year academic with Gallery Walk Method. The type of this research is Class Action Research (CAR). The action of this research is Gallery Walk Method. The location of this research is on the Class IV of the Elementary School of Bulu, Sub District of Bulu, Regency of Rembang. The period of this research are two months on the middle of the first semester of 2017/2018 year academic, begin on September 2017 to October 2017. The subjects of this research are the Class IV students of the Elementary School of Bulu on the first semester of 2017/2018 year academic as much as eleven children; consist of five boys and six girls. The data of this research are the students as the subject according to the action on the learning. Techniques of collecting data of this research are non test technique and test technique. Technique of analyzing data of this research is comparative description. The procedure of this research is cycle model by Kemmis and Mc Taggart. The results of this research are 1) the Javanese Language about the Story of Shadow Puppets need a set of tools and material such as multicolored and dark-white illustration pictures that according to the subject matter, 2) the Javanese Language about the Story of Shadow Puppets is a group learning approach that consist of three up to four members with a constant composition and place, 3) the Javanese Language about the Story of Shadow Puppets is increasing the students’ learning activities, 4) the Javanese Language about the Story of Shadow Puppets is increasing the students’ learning results.Keywords: Telling Story Ability, Learning Results, Javanese Language, Shadow Puppets, Gallery Walk Method.Abstrak Tujuan penelitian adalah 1) mendeskripsikan pembelajaran Bahasa Jawa tentang Cerita Tokoh Wayang pada peserta didik Kelas IV SDN Bulu di Semester I Tahun Pelajaran 2017/2018 dengan Metode Gallery Walk dan 2) menganalisis kemampuan bercerita dan hasil belajar Bahasa Jawa tentang Cerita Tokoh Wayang pada peserta didik Kelas IV SDN Bulu di Semester I Tahun Pelajaran 2017/2018 dengan Metode Gallery Walk. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Tindakan dalam penelitian adalah Metode Gallery Walk. Tempat penelitian ini adalah Kelas IV SDN Bulu, Kecamatan Bulu, Kabupaten Rembang. Waktu penelitian ini adalah dua bulan, pada pertengahan Semester I Tahun Pelajaran 2017/2018, mulai bulan September tahun 2017 sampai bulan Oktober tahun 2017. Subjek penelitian ini adalah peserta didik Kelas IV SDN Bulu pada Semester I Tahun Pelajaran 2017/2018 sebanyak sebelas anak, terdiri dari lima putra dan enam putri. Data penelitian adalah peserta didik sebagai subjek penelitian sesuai dengan tindakan dalam pembelajaran. Teknik pengumpulan data dengan teknik non tes dan teknik tes. Teknik analisis data dengan teknik deskriptif komparatif. Prosedur penelitian ini adalah model Siklus oleh Kemmis dan Mc Taggart. Hasil penelitian adalah 1) Pembelajaran Bahasa Jawa tentang Cerita Tokoh Wayang dengan Metode Gallery Walk membutuhkan alat dan bahan, yaitu gambar ilustrasi berwarna maupun hitam-putih yang sesuai dengan materi, 2) Pembelajaran Bahasa Jawa tentang Cerita Tokoh Wayang dengan Metode Gallery Walk dengan pendekatan belajar kelompok, yaitu tiga kelompok terdiri dari tiga sampai empat anggota dengan komposisi dan tempat yang sama, 3) Pembelajaran Bahasa Jawa tentang Cerita Tokoh Wayang dengan Metode Gallery Walk meningkatkan aktivitas belajar peserta didik, 4) Pembelajaran Bahasa Jawa tentang Cerita Tokoh Wayang dengan Metode Gallery Walk meningkatkan hasil belajar peserta didik.Kata Kunci: Kemampuan Bercerita, Hasil Belajar, Bahasa Jawa, Wayang, Metode Gallery Walk.